A Combined Family of Ratio Estimators for Population Mean using an Auxiliary Variable in Simple Random Sampling - Uraiwan Jaroengeratikun; Nuanpan Lawson (Institute for Research and Community Services (LPPM) ITB, 2019)
This paper proposes two new classes of ratio estimators for population mean when information on a known auxiliary variable is available in simple random sampling. A combined family of ratio estimators for estimating population mean by combining the two new estimators together in order to minimize the mean square error (MSE) is then suggested. The expressions for the bias and mean square error of all proposed estimators up to the first order of approximation were obtained. The performance of the proposed estimators was compared with that of existing estimators using both a theoretical and a simulation study. The proposed family of estimators was found to be more efficient than the existing estimators.